2018
DOI: 10.1245/s10434-018-6575-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved False-Negative Rates with Intraoperative Identification of Clipped Nodes in Patients Undergoing Sentinel Lymph Node Biopsy After Neoadjuvant Chemotherapy

Abstract: The study results also suggest that axillary dissection could be omitted for patients presenting initially with N1 disease and with a negative clipped node as the SLN after NAC due to the low FNR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 18 publications
5
23
0
1
Order By: Relevance
“…The FNR observed in cN1 patients was 4.2% when the clipped node was recognized as SLN, increasing to 16.7% if the removed clipped node did not correspond to the SLN. It concluded the validity of omission of ALND in patients whose nodes are clinically positive patients before NAC, become subsequently negative, if the negative clipped node is identified as SLN [41] .…”
Section: Neoajuvant Chemotherapymentioning
confidence: 97%
“…The FNR observed in cN1 patients was 4.2% when the clipped node was recognized as SLN, increasing to 16.7% if the removed clipped node did not correspond to the SLN. It concluded the validity of omission of ALND in patients whose nodes are clinically positive patients before NAC, become subsequently negative, if the negative clipped node is identified as SLN [41] .…”
Section: Neoajuvant Chemotherapymentioning
confidence: 97%
“…Morency et al [ 15 ] reported that post-NAC axillary US was not appropriate as a standalone staging procedure in patients who present with N+ breast cancer. Previous studies emphasizing the importance of pre-NAC marking reported that the correct nodes were easily identifiable by US and other methods if metastatic nodes were properly marked before NAC [ 8 11 12 13 16 17 ]. These procedures should be done by an experienced breast-dedicated radiologist who identifies clipped nodes with a high success rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, SNB has been subsequently proven to be more accurate in cN1 patients who undergo NAC if - two or more nodes are removed, the clipped node is removed and immunohistochemistry is used. As a result, patients undergoing NAC can be down-staged in the axilla and ALND can potentially be avoided [ [43] , [44] , [45] ]. The same could be said for patients with pOBC, particularly if they are already considered to be in a better prognostic group than those patients with T1N1 disease [ 25 , 26 ].…”
Section: Diagnostic Techniques and Their Effect On The Incidence And mentioning
confidence: 99%